2018
DOI: 10.25179/tjem.2017-58803
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Thyrotropin to Thyroglobulin as a Novel Marker for Differentiating Between Benign and Malignant Thyroid Nodules within Different Bethesda Categories

Abstract: Objective: We aimed to determine whether the ratio of thyrotropin (TSH) to thyroglobulin (Tg) (TSH/Tg) would be able to assist in predicting malignancy in thyroid nodules. Material and Methods: Euthyroid patients operated between the year 2007 and 2014 were retrospectively reviewed. Patients who previously had thyroid disease or surgery and those with increased levels of anti-thyroglobulin antibodies were excluded from this study. Clinicopathological features, as well as serum TSH, Tg, and TSH/Tg were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Specifically, Tam et al reported that the median and range values in the benign and malignant group were 0.02 μIU/ng (0.001-1.09) and 0.04 (0.001-2.24) respectively (P<0.001). 13 Similar results were reported by Yazici et al (0.02 (0.004-8.6) vs 0.04 (0.002-19) μIU/ng respectively, P=0.024). 14 Wang et al .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Specifically, Tam et al reported that the median and range values in the benign and malignant group were 0.02 μIU/ng (0.001-1.09) and 0.04 (0.001-2.24) respectively (P<0.001). 13 Similar results were reported by Yazici et al (0.02 (0.004-8.6) vs 0.04 (0.002-19) μIU/ng respectively, P=0.024). 14 Wang et al .…”
Section: Resultssupporting
confidence: 87%
“…Reviewing the data of the literature we observed that at least two studies reported significant differences in TSH/Tg ratios between patients with benign and malignant disease, although they were discrete with a very large range. 13 , 14 This latter observation significantly hinders the application of this ratio to clinical practice as a diagnostic and surveillance biomarker. Most of the studies failed to report actual 95% confidence intervals with their results being potentially affected by significant outliers; hence, it remains unknown whether the range of the true value of these ratios is associated with clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the cutoff value for TG/TSH was determined as 29.67. In their study with 244 malignant patients, Tam et al [ 16 ] reported that the TSH/TG ratio could be used as a novel marker to differentiate benign and malignant thyroid nodules in the pre-operative period and that it could help to determine the malignancy risk in nodules with indeterminate cytology and help the management of these patients. Wang et al [ 12 ] found that increased serum TSH/TG (cutoff=0.024) in the pre-operative period was associated with thyroid malignancies at a higher rate compared to TSH alone.…”
Section: Discussionmentioning
confidence: 99%